The effect of silver nanoparticles on zebrafish embryonic development and toxicology - Xia, Guangqing; Liu, Tiantian; Wang, Zhenwei; Hou, Yi; Dong, Lihong; Zhu, Junyi; Qi, Jie (Artificial cells, nanomedicine, and biotechnology, 2016)
The unique physical and chemical characteristics of nanomaterials, such as the effects of their small size, surface effects, very high rates of reaction, and quantum tunnel effect, have aroused great interest among scholars. However, improper usage has led to an increasing number of nanomaterials entering the environment through various channels, greatly threatening the security of the ecological environment and human health. The urgent need for a scientific assessment of their biosafety can enable nanomaterials to truly benefit humanity. However, the current research in this field is extremely limited with regard to safety standards and waste disposal. In this study, we used silver nanoparticles (nano-Ag) and zebrafish embryos as experimental subjects, and we have reported the deleterious effect on zebrafish embryos treated with different concentrations of nano-Ag, with respect to morphological features (mortality, deformity rate, and heartbeat) and the analysis of expression of relevant genes (sox17, gsc, ntl, otx2); we found a dose-dependent increase in mortality and hatching delay. The results of in situ hybridization indicated that nano-Ag causes a dose-dependent toxicity in embryonic development, and would affect their development and lead to deformity, delayed development, and even death. The safety limit for the concentration of nano-Ag was found to be less than 5 mg/L.